Cancer-related information needs and treatment decision-making experiences of people with dementia in England: a multiple perspective qualitative study. Issue 4 (12th April 2018) - McWilliams, Lorna; Farrell, Carole; Keady, John; Swarbrick, Caroline; Burgess, Lorraine; Grande, Gunn; Bellhouse, Sarah; Yorke, Janelle
Abstract : Objectives: Little is known about the cancer experience and support needs of people with dementia. In particular, no evidence currently exists to demonstrate the likely complex decision-making processes for this patient group and the oncology healthcare professionals (HCP) involved in their care. The aim of this study was to explore the cancer-related information needs and decision-making experiences of patients with cancer and comorbid dementia, their informal caregivers and oncology HCPs. Design: Cross-sectional qualitative study. Semistructured interviews were conducted face to face with participants. Interviews were audio recorded and transcribed prior to thematic analysis. Setting: Patients with a diagnosis of cancer and dementia, their informal caregivers and oncology HCPs involved in their care, all recruited from a regional treatment cancer centre. Participants: Purposeful sample of 10 patients with a diagnosis of cancer–dementia, informal caregivers (n=9) and oncology HCPs (n=12). Results: Four themes were identified: (1) leading to the initial consultation—HCPs require more detailed information on the functional impact of dementia and how it may influence cancer treatment options prior to meeting the patient; (2) communicating clinically relevant information—informal caregivers are relied on to provide patient information, advocate for the patient and support decision-making; (3) adjustments to cancer care—patients with dementia get through treatment with the help of their family and (4) following completion of cancer treatment—there are continuing information needs. Oncology HCPs discussed their need to consult specialists in dementia care to support treatment decision-making. Conclusions: Although patients with cancer–dementia are involved in their treatment decision-making, informal caregivers are generally crucial in supporting this process. Individual patient needs and circumstances related to their cancer must be considered in the context of dementia prognosis highlighting complexities of decision-making in this population. Oncology teams should strive to involve healthcare staff with dementia expertise as early as possible in the cancer pathway.